Vitamin E profile of three varieties of Cucumis melo L.: pulp and by-products - Silva, M.A. (2021)
The development of new food products based on the use of fruit by-products is a relevant topic nowadays. Indeed, it is a sustainable solution for the reduction of food losses and waste, as well as for the environmental impact. Cucumis melo L. is a very popular fruit worldwide, due to its excellent sensory and nutritional qualities. On the other hand, it contains a large amount of seeds and peel (by-products) that, until now, have been discarded. These by-products are a rich source of compounds with high antioxidant activity and beneficial properties for human health, such as vitamin E [1]. The aim of this study was to determine the vitamin E profile of pulp and by-products (peel and seeds) of three different Cucumis melo L. varieties (Grand Prix, Soleares and Waikiki). In addition, the vitamin E profile was compared for the Soleares variety at two different seasons (Soleares-I, winter and Soleares-P, spring). The Cucumis melo L. fruits were collected from major supermarket chains in the Lisbon region (Portugal). Vitamin E profile was analysed by HPLC-DAD-FLD, according to the method described by Alves et al. [2]. The results show that γ-tocopherol and α-tocopherol are the main vitamers present in Cucumis melo L. by-products (seeds and peels). The total vitamin E content varied between 6.69 mg/100 g (Grand Prix) and 19.1 mg/100 g (Soleares-P) for Cucumis melo L. seeds and between 3.57 mg/100 g dry weight (Soleares-P) and 25.0 mg/100 g dry weight (Grand Prix) for the peel. For Cucumis melo L. pulp, the levels of vitamin E ranged between 0.78 mg/100 g dry weight (Waikiki) and 1.11 mg/100 g dry weight (Grand Prix). In summary, Cucumis melo L. by-products can be used to enrich and create novel foods, improving their nutritional value and enhance their health promoting properties. It was shown that the contents of vitamin E can contribute for this possible valorization.